Manajemen Unit Usaha Pesantren Berbasis Ekoproteksi (Studi Kasus di Pondok Pesantren Al-Ihya Ulumuddin Kesugihan Cilacap) - Siti Nur Azizah (Al-Tijary, 2016)
Management of units based business ekoproteksi in boardingschool is a process to increase the assets and capabilities boarding school in economics to go independence Management of units based business ekoproteksi in boarding school. (Islamic Boarding School of Managment) is a management program by using a bottom-up approach, the implementation of activities in the field on the initiative and inspiration of the people. Based on the assumption that the pesantren community better understand their needs so that people involved in the making of pesantren management program that is appropriate management program.In theory Bottom Up in the boarding school, Kyai, the Government, as the creator of the means to achieve the aspirations of the people boarding school. The economic management of boarding schools has started to be realized in practice management program making such suggestions and input on community needs boarding school itself and then by the authors analyzed using the theory of management. Management process the government in terms of management must be implemented by public boarding school, so the people here besides serving as executor of the policy as well as giving a response back on the policy made by Kyai and government. Boarding school is now generally a boarding school who was managing the assets of the local economy that aims to empower economically boarding school, for the existence and economic welfare of boarding schools, students, citizens around the pesantren. On this basis, the Management Boarding economically requires a protection (protection / defense) for the sake of continuity and smoothness of its management.